An Analysis Of Code Switching Of Diaspora In Podcast Cinta Laura In Channel Youtube “Puella Id” - Rifky Wulan Aprinyza (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
This study focuses the phenomenon of code switching in Puella ID youtube channelbecause in the podcast Cinta Laura used Indonesian language as the first language in their conversations. The researcher takes the speaker’s utterances when they switch in one language to another. She switch two language when her talk with guest star Karin Novilda or commonly called Awkarin. In a bilingual community, people often switch from one language to another in their daily conversations and the use of code-switching often reflects the social or cultural identities of the speakers. The switch to a particular language in the bilingual discourse can also be employed as an effective vehicle to signal ethnic identity. The Aim of this research is to identify and to analyze functions of code-switching used in Cinta Laura’s podcast on Puella ID YouTube channel. This research uses documentary technique and Gumprez (1982) taxonomy. The results as many as 39 data are collected. Show that there are Quotation 3%, Addressee Specification 21%, Interjection 10%, Reiteration 3%, Message Qualification 13%, and Personalization vs Objectivization 51%. The most functions found in this research are Personalization and Objectivization.